2014
DOI: 10.7731/kifse.2014.28.4.029
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Validity of Scaling Law for Compartment Fires

Abstract: In this study, to assess the validity of scaling law which was based on the ventilation factor and utilized in fields of compartment fires, numerical simulations were conducted on full-and 2/5 reduced-scale compartment fires using FDS and simulation results were compared with the previously published experimental data. The numerical modeling used in this study was verified by comparing the predicted temperature at several points of the upper layer with the experiment data. Temperature and concentration distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Prototype Model [3,5,6,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Simulation [24][25][26][27] Form of Architecture…”
Section: Research Trends and Error Rate Analysis Methodsmentioning
confidence: 99%
“…Prototype Model [3,5,6,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Simulation [24][25][26][27] Form of Architecture…”
Section: Research Trends and Error Rate Analysis Methodsmentioning
confidence: 99%
“…The validity and accuracy of the scaling law were examined in some studies. For example, Ko [11] conducted large-scale and small-scale compartment fire numerical simulations for existing experimental studies [12,13] to evaluate the effectiveness of the scaling law based on the ventilation parameters applied to compartment fire studies. The results of the analysis confirmed that the flow pattern, ejected flame behavior, and temperature distribution characteristics inside the compartment were similar between the large-scale and small-scale models.…”
Section: Parametermentioning
confidence: 99%